VOCABULARY GROWTH THROUGH INDEPENDENT READING: A CASE STUDY OF EFL STUDENTS - Ufairoh Rozana Nabilah; Nirwanto Maruf (Universitas Kuningan, 2025)
This study investigates the relationship between independent reading frequency and vocabulary growth among EFL students at Universitas Muhammadiyah Gresik. Using a quantitative research design, data were collected from 50 undergraduate students majoring in English through a close-ended questionnaire. The results of this study underscore the critical role that regular independent reading plays in enhancing vocabulary acquisition and overall language proficiency among EFL students. Specifically, the strong positive correlation between reading frequency and vocabulary growth (r = 0.62, p < 0.01) indicates that students who engage in independent reading activities more frequently tend to experience greater improvements in their vocabulary. This finding is further supported by the subgroup analysis, which revealed that reading books and academic articles had the strongest correlation with vocabulary growth (r = 0.65, p < 0.01 for books; r = 0.58, p < 0.01 for academic articles). These materials often provide rich and varied contexts for encountering new words, which facilitates deeper understanding and retention. The findings highlight the need for educational strategies that encourage all students to read more frequently and diversely. Future research could explore additional factors that influence reading habits and vocabulary growth among EFL students. For instance, studies could investigate the impact of motivation, reading interest, and the availability of reading materials on students' reading frequency and vocabulary acquisition. Additionally, research could examine the role of socio-cultural factors, such as family background and peer influence, in shaping reading habits. Furthermore, longitudinal studies could track changes in reading frequency and vocabulary growth over time to provide insights into the long-term effects of independent reading.